2012
DOI: 10.1002/bdd.1775
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and excretion studies of oral administered naringin, a putative antitussive, in rats and dogs

Abstract: Naringin, a major active flavonone glycoside from a traditional Chinese medicine Huajuhong, has been demonstrated to have activities such as peripheral antitussive, mucoregulator and anti-inflammatory. The purpose of this study was to elucidate the metabolism and mass balance of orally administered naringin in rats and dogs. After oral administration of naringin to rats and dogs at doses of 42 mg/kg and 12.4 mg/kg, respectively, metabolites in excreta were identified using a LC-Q-TOF system. The major metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 25 publications
(39 reference statements)
2
43
0
Order By: Relevance
“…In pharmacokinetic studies, naringin was administered orally to rats at a dose of 42 mg/kg, which was converted from 36.8 mg/kg in guinea pigs [23,24]. Thus, the middle dose (18.4 mg/kg) was chosen in the present study based on pharmacodynamic and pharmacokinetic studies.…”
Section: Discussionmentioning
confidence: 99%
“…In pharmacokinetic studies, naringin was administered orally to rats at a dose of 42 mg/kg, which was converted from 36.8 mg/kg in guinea pigs [23,24]. Thus, the middle dose (18.4 mg/kg) was chosen in the present study based on pharmacodynamic and pharmacokinetic studies.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the metabolites are transported, mainly via the portal vein, to the liver for further biotransformation to glucuronide and sulphate conjugates, which enter systemic circulation (Tsai and Tsai, 2012). Finally, naringin, naringenin, and their conjugates are secreted into bile and excreted into the feces or reabsorbed to become systemically available (i.e., through enterohepatic circulation) (Ma et al, 2006;Liu M. et al, 2012;Zeng et al, 2017). Since the glucuronide and sulphate conjugates of flavonoids were reported as precursors of bioactive metabolites (glycoside or aglycone) (Terao et al, 2011;Matsumoto et al, 2018), hydrolysis with b-glucuronidase is often used in pharmacokinetic studies of naringin or naringenin.…”
Section: Introductionmentioning
confidence: 99%
“…The flavonoid naringin (NAR; 4' ,5,7-trihydroxyflavanone-7-rhamnoglucoside) is a polyphenolic compound that naturally occurs in citrus fruit. NAR has previously been shown to have anti-inflammatory (17,18), antioxidant (19,20), anticancer (21), antibacterial (22), antimutagenic (23), antiulcer, antitussive (24,25), neuroprotective (26)(27)(28), as well as antihypertensive properties (29), and can reduce blood cholesterol levels, preventing thrombosis (30). In recent years, it has been reported that NAR inhibits the apoptosis of hydrogen peroxide-induced p388 cells (31) and Rotenone-induced human neuroblastoma SH-SY5Y cells (32).…”
Section: Introductionmentioning
confidence: 99%